HE INFLUENCE OF EXPERIENTIAL VALUE AND EXPERIENTIAL QUALITY ON REVISIT INTENTION OF WATERFRONT CITY PANGURURAN SAMOSIR REGENCY - Inriani Siallagan; Alfifto (RADJA PUBLIKA, 2025)
This article aims to determine the effect of Experiential Value on revisit intention at Waterfront City Pangururan, Samosir Regency. To determine the effect of Experiential Quality on revisit intention at Waterfront City Pangururan, Samosir Regency. To determine the effect of Experiential Value and Experiential Quality on revisit intention at Waterfront City Pangururan, Samosir Regency. The type of research used in this study is a quantitative associative approach. In this study, the population is all visitors totaling 242,028 tourists who have visited the Waterfront City Pangururan, Samosir Regency tourist attraction throughout 2024 and the sample determination using the Slovin formula in this study the number of samples is rounded to 100 respondents. The sampling technique in this study was carried out using non-probability and purposive sampling techniques. Data collection techniques through distributing questionnaires to obtain primary data and documentation to obtain secondary data. The statistical data analysis technique used is multiple linear regression and previously carried out classical assumption tests and validity and reliability instrument tests. As well as determination testing and hypothesis testing. The results of the study show that the experiential value variable partially has a positive and significant effect on revisit intention at the Waterfront City Pangururan tourist attraction in Samosir Regency. The experiential quality variable partially has a positive and significant effect on revisit intention at the Waterfront City Pangururan tourist attraction in Samosir Regency. The experiential value and experiential quality variables partially have a positive and significant effect on revisit intention at the Waterfront City Pangururan tourist attraction in Samosir Regency.